Determinants Of Profitability Of 10 Big Banks In Indonesia With Eagles Analysis - Ristanti, Erakusari Dheni; Ismiyanti, Fitri (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to identify the determinants of profitability of the 10 largest banks in Indonesia over 10 years (2010 to 2019). These 10 banks were selected because they are the beacon of health to the national banking sector and the economy. The EAGLES framework was applied to the analysis. A multiple regression equation was formulated using SPSS software to analyze the strength of correlation of nine independent financial indicators to the dependent variable, return of assets (ROA). These financial indicators are listed as Non-Performing Loan (NPL), Non-Performing Loan Growth (NPLG), Loan Growth (LG), Deposit Growth (DG), Staff Cost Growth (SCG), Loan Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), and Net Interest Margin / Net Operating Cost (NIM-NOC). The analysis found four independent financial indicators that are statistically significant as having a strong association with the ROA. The contribution of the finding is that the Indonesian banks can be guided to focus on these four indicators on their management dashboard to steer their profitable growth. Another contribution is that the central bank authorities can also be informed of these same indicators as a tool to manage the safety of the Indonesian banking sector.